042. Colonic Duplication with Recto-Vestibular Fistula: A Case Report - Fitriansyah, Muhammad Noor; Soenjoto, Dadik Agus (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p042, 2024)
Background : Anorectal malformations associated with colonic duplications are a rare condition. Colonic duplication may have different presentations according to its location and size, with an incidence of less than 15% of all gastrointestinal duplications. Colonic duplication is less common than ileal duplication, whether cystic or tubular. Duplications are considered congenital malformations because they are thought to arise from disturbances in embryonic development. This report aims to present and analyze the clinical presentation, diagnostic approach, and management of anorectal malformations associated with colonic duplications in an 11-month-old child at our hospital, highlighting the challenges and treatment strategies for such a rare case. Case : We present a case of an 11-month-old girl, referred from a network hospital with a post-colostomy at 4 months of age for recto-vestibular fistula with findings of colonic duplications at colostomy. Exploratory laparotomy was performed until the colonic duplications were identified and completely resected. Conclusion: Colonic duplication is a rare congenital disorder, and its association with anorectal abnormalities is even rarer. The surgical treatment includes resection of the duplicated colon. Surgical intervention is the treatment of choice.